PENANGANAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS DI KLINIK KARYA SUCI - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Desri Friti Anita Purba; Alexander Marbun (Nusantara Hasana Journal, 2022)
This community service activity at the Karya Suci Clinic aims to address and improve the quality of life of patients with osteoarthritis through the implementation of physiotherapy interventions. Methods used include patient education, exercise therapy, manual techniques (such as joint mobilization and manual traction), and the use of physical modalities to reduce pain and improve joint function. This activity involves a comprehensive patient assessment following clinical evaluation standards, followed by a four-week physiotherapy program. Monitoring is carried out by measuring pain intensity, joint stiffness, and functional ability using instruments such as the WOMAC score. Results obtained show a significant reduction in pain intensity, increased range of motion, and improved quality of life for patients. This report presents a comprehensive overview of the intervention process and an analysis of the results obtained in the treatment of osteoarthritis at the clinic.